Forest schools: moving towards an alternative pedagogical response to the Anthropocene?. Issue 3 (3rd May 2020) - Mycock, Katherine
ABSTRACT: In this paper I consider whether forest schools provide a space where we could rethink pedagogy in the Anthropocene. I explore the challenges and possibilities of thinking beyond the business-as-usual of human-centric pedagogies drawing upon an ethnographic study of two forest schools, located in the West Midlands of England conducted in 2014–2015. I take a more-than-social approach, which moves beyond narrow essentialist constructions of nature and childhood. I use both Barad's theory of agential realism, to explore children's lively intra-actions with more-than-humans at forest school, and Haraway's concept of worlding, to examine collective world making and remarking. Through this conceptual framing I explore whether forest schools are or could become a space for more-than-social pedagogies in which children might imagine and care for other worlds. If so, how might this kind of other-world imagining and caring gesture towards an alternative pedagogical response to the Anthropocene?